Corporate Governance, Risiko, dan Nilai Perusahaan Pada Perusahaan Sektor Perbankan Di Indonesia - amalutstsani, wulida yusr; Anwar, Muhadjir (Jurnal Ilmu Manajemen, 2021)
This study aims to determine the influence of corporate governance, risk on firm value, and the influence of corporate governance on risk in banking sector companies which are listed in Indonesia Stock Exchange during 2017-2019 periods. The populations are banking sector companies listed in Indonesia Stock Exchange. The sample collection technique has been done by using purposive sampling method, 40 companies were obtained from 43 banking sector companies. The analyzing tool that used in this study was path analysis with SPSS program. The study found that corporate governance give positif and significant influence on firm value, risk give non significant influence on firm value, and corpotrate governance give negative and significant influence on risk. In additional, this study also found that risk does not mediated the influence of corporate governance and firm value.